Physicochemical and functional properties of Lycium ruthenicum pectin by different extraction methods - Wu, Ziyang; Qin, Dan; Li, Hehe; Guo, Dongqi; Cheng, Huan; Sun, Jinyuan; Huang, Mingquan; Ye, Xingqian; Sun, Baoguo (Frontiers in Nutrition, 2022)
Three different extraction methods were used to extract high-temperature water-extracted pectin (HWp), high-temperature acid-extracted pectin (HAp) and high-temperature alkali-extracted pectin (HALp) in Lycium ruthenicum. The physicochemical properties, structure and functional properties of three different pectin were studied. The results showed that the methods of HWp and HALp can extract rhamnogalacturonan-I (RG-I) in Lycium ruthenicum better. Through structural features analysis, HWp and HALp has a branched structure, and HWp has a higher degree of esterification than HAp and HALp. Zeta potential results show that HWp solution is more stable. The thermal analysis results show that the thermal stability is HALp>HAp>HWp. HWp has the highest viscosity. The inhibitory activity results showed that HWp, HAp and HALp have a certain inhibitory effect on α-glucosidase activity. This study provides the effects of different extraction methods on the properties of Lycium ruthenicum pectin, and aims to provide a theoretical basis for the pharmaceutical and food industries to choose more suitable pectin extraction methods.